Long-term operation of electro-biocatalytic reactor for carbon dioxide transformation into organic molecules. (October 2018) - Srikanth, Sandipam; Kumar, Manoj; Singh, Dheer; Singh, M.P.; Puri, S.K.; Ramakumar, S.S.V.
Highlights: Electro-biocatalytic CO2 transformation to organics was studied for 320 days. Stabilized biocathode of selectively enriched culture was studied for electro-synthesis. CO2 availability in soluble form dictated the product slate. Electron transfer is possibly H2 mediated and DET with bicarbonate but restricted to DET with CO2 . CE was high irrespective of carbon nature but CCE significantly varied for CO2 and bicarbonate. Abstract: Electro-biocatalytic reactor was operated using selectively enriched mixed culture biofilm for about 320 days with CO2 /bicarbonate as C-source. Biocathode consumed higher current (−16.2 ± 0.3 A/m 2 ) for bicarbonate transformation yielding high product synthesis (0.74 g/l/day) compared to CO2 (−9.5 ± 2.8 A/m 2 ; 0.41 g/l/day). Product slate includes butanol and butyric acid when CO2 gets transformed but propionic acid replaced both when bicarbonate gets transformed. Based on electroanalysis, the electron transfer might be H2 mediated along with direct transfer under bicarbonate turnover conditions, while it was restricted to direct under CO2 . Efficiency and stability of biofilm was tested by removing the planktonic cells, and also confirmed in terms of Coulombic (85–97%) and carbon conversion efficiencies (42–48%) along with production rate (1.2–1.7 kg/m 2 electrode) using bicarbonate as substrate. Selective enrichment of microbes and their growth as biofilm along with soluble CO2 have helped in efficient transformation of CO2 up to C4 organic molecules.